Suppression of green mould rot caused by Penicillium digitatum in kinnow fruits by hot water immersion treatment - A.K. THAKUR, DINESH SINGH and (Indian Phytopathology, 2002)
Kinnow fruits showed minimum incidence of green mould rot disease (Penicillium digitatum) (44.5%) and infected area 2.4 cm in fruits treated with hot water 50°C for 2 min and GO°Cfor 45 sec within 3 days. No fruit was found to be decayed in the treatment at 50°C for 2 min up to 90 days storage while in case at 55°C for 1 min and GO°Cfor 45 sec all fruits were rotted within 30 days. The fruit quality was also better at 50°C for 2 min as compared to other treatments.